Risk analysis of depression among adult patients with epilepsy of different sex: a retrospective single-center study from China - Guo, Wang; Li, Yu-xuan; Zhang, Yi; Lv, Xue-rui; Wang, Sheng-xue; Zhang, Shuang-yuan; Wang, En-si; Chen, Xin-jie; Li, Yun (Frontiers in Psychiatry, 2023)
Objective: To determine sex differences in the prevalence of depression and assess the risk factors for depression among adult patients with epilepsy from the Dali area of China.: We retrospectively analyzed the clinical data of adult patients with epilepsy who visited the First Affiliated Hospital of Dali University from January 2017 to January 2022. Patient Health Questionnaire-9 was used to assess depressive symptoms in patients with epilepsy. The risk factors of depression were analyzed by binary logistic regression among different sex in patients with epilepsy.Results: There were significant sex differences in depression in patients with epilepsy (P < 0.001), and females were 4.27 times more likely to suffer from depression than males (95% confidence interval: 3.70-4.92). The risk factors for depression among female patients with epilepsy included occupation (P < 0.001), years with epilepsy (P < 0.001), seizure frequency (P < 0.001), seizure type (P < 0.001), etiology (P < 0.001), number of antiseizure medications used (P < 0.001), antiseizure medications (P < 0.001), and electroencephalogram findings (P < 0.001). The risk factors for depression among male patients with epilepsy included age (P < 0.001), ethnicity (P < 0.001), occupation (P < 0.001), years with epilepsy (P < 0.001), seizure frequency (P < 0.001), seizure type (P < 0.001), etiology (P < 0.001), number of antiseizure medications used (P < 0.001), antiseizure medications (P < 0.001), and electroencephalogram findings (P < 0.001).Adult female patients with epilepsy had a higher risk of depression than adult male patients with epilepsy. There were sex differences in the risk factors associated with depression among patients with epilepsy.